Correlation Studies on Seed Yield and Fruit Weight Of Four BT Eggplant Varieties - Hasan, MK; Hoque, MO; Islam, MR; Khanam, D; Alam, MS (Bangladesh Journal of Agricultural Research, 2022)
Abstract not available Bangladesh J. Agril. Res. 45(1): 89-92, March 2020